Pharmaceutical drugs and their environmental footprint: an exploratory study of medicine waste management. - Fontana, Marcela (2025)
[Introduction]: Pharmaceutic contamination is a growing global concern, and Latin America is no exception. However, information specific to this phenomenon in the region remains scarce. This study addresses one aspect of the problem: the generation and management of pharmaceutical waste in healthcare settings. [Objective]: To characterize the generation and management of pharmaceutical waste produced by healthcare institutions, including community pharmacies, healthcare facilities with and without inpatient services, pharmaceutical distributors, and veterinary clinics. Additionally, to analyze the operations and regulations governing this waste in regulatory entities within the city of Neuquén, Argentina (2023). [Methodology]: Observational, cross-sectional,and prospective study. Data collection involved validated surveys applied to a proportional stratified sample of 114 healthcare establishments and interviews with representatives of regulatory entities. [Results]: All establishments comply with current environmental regulations. Pharmaceutical distributors demonstrate superior management, excelling in traceability, standardization, and training. While stock control is utilized, there are few secondary strategies to reduce waste and insufficient material recovery. Municipal initiatives and attitudes towards controlling this phenomenon are positive but lack support from higher levels of government. [Conclusions]: The management of pharmaceutical waste in the healthcare institutions studied shows room for improvement. According to the variables analyzed, the use of recommended tools and strategies for quality management is limited. A positive municipal commitment to addressing the issue was identified, but this is not reflected at all governmental levels. Furthermore, the perception and awareness of pharmaceutical contamination and its risks remain low among stakeholders in the pharmaceutical use chain.